Multicenter comparison of MicroScan and BACTEC blood culture systems. - Wasilauskas, B (1987)
Recently, MicroScan (Baxter MicroScan Div., W. Sacramento, Calif.) introduced a radiolabeled-blood-culture system that is compatible with the BACTEC 460 (Johnston Laboratories, Inc., Towson, Md.). A multicenter blood culture study was initiated to evaluate this new system. Approximately 20 ml of blood was obtained from each patient and divided equally between BACTEC and MicroScan bottles which were incubated and processed identically. Aerobic bottles were examined twice on days 1 and 2 and once on days 3, 4, 5, 6, and 7. Anaerobic bottles were examined once a day for 7 days. There were 3,451 cultures evaluated, and 414 of these subsequently grew microorganisms. Of these positive cultures, 64 were judged to be contaminated. Of the remaining 350 positive cultures, 253 grew in both systems, 54 grew in BACTEC bottles only, and 43 grew in MicroScan bottles only. The average times to detect positive cultures were 1.8 and 2.1 days by the BACTEC and the MicroScan systems, respectively. No significant difference in the number or kind of organisms recovered or in the detection times for positive cultures was observed between the two blood-culturing systems.